Sepiolite, a potential excipient for drugs subject to oxidative degradation - Hermosin, M C; Cornejo, J; White, J L; Hem, S L (Journal of pharmaceutical sciences, 1981)
Sepiolite, a member of the fibrous mineral group of clays, is relatively free of surface ferric iron and does not accelerate significantly the oxidative degradation of hydrocortisone. The compatibility of sepiolite with drugs that can undergo oxidative degradation is in sharp contrast to the catalytic effect of attapulgite, another fibrous mineral, which contains a significant amount of surface ferric iron and which therefore accelerates oxidative degradation. Sepiolite adsorbs hydrocortisone by a weak adsorption mechanism, which was shown by IR spectroscopy to be chiefly due to hydrogen bonding. However, accelerated oxidative degradation of the adsorbed hydrocortisone does not occur. Maximum adsorption occurs at pH 7-8.5. Desorption occurs readily by washing with water. Sepiolite has similar rheological properties to attapulgite. The results of this study suggest that sepiolite may be useful as a pharmaceutical excipient for drugs that undergo oxidative degradation.